2012
DOI: 10.1542/peds.2011-1854
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Sweet Syndrome: A Potential Marker of Serious Systemic Illness

Abstract: Sweet syndrome is an inflammatory disease characterized by fever and painful erythematous plaques with a dermal neutrophilic infiltrate. It is most common in adults, where it is often parainflammatory or paraneoplastic, but is rare in children. We describe 3 cases of neonatal Sweet syndrome, including 1 patient who had myelodysplastic syndrome and immunodeficiency, the first report of a premalignancy underlying infantile Sweet syndrome. We reviewed the literature on patients presenting with neutrophilic dermat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 25 publications
1
26
0
2
Order By: Relevance
“…Interestingly, all of them were <1‐year‐old infants (at the age 2, 6 and 7 months). In the literature, neutrophilic diseases involving the upper airways and causing respiratory distress have reported in two additional patients presenting with PG and one with SS . Similar to our observations in this study, ENT involvement (laryngeal lesions) occurred before the age of one year in both cases (at the age of 4 and 9 months) and caused severe respiratory distress.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, all of them were <1‐year‐old infants (at the age 2, 6 and 7 months). In the literature, neutrophilic diseases involving the upper airways and causing respiratory distress have reported in two additional patients presenting with PG and one with SS . Similar to our observations in this study, ENT involvement (laryngeal lesions) occurred before the age of one year in both cases (at the age of 4 and 9 months) and caused severe respiratory distress.…”
Section: Discussionmentioning
confidence: 96%
“…The average age of onset of SS in children is 5 years. Contrary to the female dominance in adults, there is reported to be an equal sex predisposition in children, with a male dominance in infants . A diagnostic criteria for SS was put forth by von den Driesch in 1994 (Table ) .…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the female dominance in adults, there is reported to be an equal sex predisposition in children, with a male dominance in infants. [4][5][6] A diagnostic criteria for SS was put forth by von den Driesch in 1994 (Table 1). 1 Our patient had onset of lesions at the age of 13 months, and fulfilled the criteria proposed for SS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sweet syndrome in children is rare, accounting for approximately 5% of all cases. Neonatal and infantile Sweet syndrome are even more uncommon; a 2012 review found 12 infants presenting within the first 8 weeks of life . It is characterized by rapid onset of tender erythematous papules or plaques with a predominant neutrophilic infiltrate on histopathology without leukocytoclastic vasculitis.…”
Section: What Is the Diagnosis?mentioning
confidence: 99%